Training program for female community volunteers to combat COVID 19 in rural Nepal - Ramu Kharel; Soniya P. Regmi; Timmy Lin; Adam C. Levine; Adam R. Aluisio (Taylor & Francis Group, 2022)
Female Community Health Volunteers (FCHV) in Nepal have identified lack of appropriate training as a barrier to involvement in the COVID 19 response. With more than 50,000 FCHVs serving rural areas of Nepal, they are instrumental in healthcare and are a major source of information delivery to those with the most limited health-care access in Nepal. This communication describes an innovative training programme to rapidly equip FCHVs with knowledge on COVID 19 response. The ongoing programme leverages partnerships between local municipalities and a local community-based organisation and has rapidly trained more than 300 FCHVs across four districts with a population of 1,000,000, and has plans to expand the training across the country. This training programme is a key example of how local partnerships can be utilised for digital training of FCHVs in remote parts of Nepal and leveraged to strengthen response capacity during the pandemic.